The Character of Peace in Judges’ Customary Criminal Receptions as Restorative Justice - Hazar Kusmayanti; Sherly Ayuna Putri; Efa Laela Fakhriah; Ramalinggam Rajamanickam (Faculty of Law, Universitas Negeri Semarang, Indonesia, 2024)
The idea that restorative justice primarily derives from indigenous communities' beliefs, which have existed for a very long time and have evolved into customary law from generation to generation, gave rise to the term restorative justice in Indonesia. According to Article 5 paragraph (1) of the Judicial Power Law, it is the duty of the judge to investigate, adhere to, and comprehend the legal values and sense of justice that exist in society. The author of this study will examine how judges in courts use restorative justice in the process of interpreting local customary law to avoid conflicts with it. And discover what challenges judges in court face in accepting this customary law. The author's research strategy is normative juridical and is based on primary, secondary, and tertiary legal resources. According to research, district court judges can significantly contribute to the realization of restorative justice in the context of customary criminal law by having a thorough understanding of customary law, employing a mediation approach, enforcing restorative sanctions, offering education and counseling; and placing a high priority on reconciliation. The current national criminal justice system can be viewed as failing to represent the interests of victims. The social background of the judge's origin, the judge's educational background, the judge's ethnicity, and the environment at the time of the hearing are all barriers to judges accepting customary law in their decisions.